Axions as a probe of solar metals - Jaeckel, Joerg; Thormaehlen, Lennert J. (Physical review, 2019)
Axion helioscopes aim to detect axions which are produced in the core of the Sun. Their spectrum contains information about the solar interior and could in principle help to solve the conflict between high and low metallicity solar models. Using the planned International Axion Observatory as an example, we show that helioscopes could measure the strength of characteristic emission peaks caused by the presence of heavier elements with good precision. In order to determine unambiguously the elemental abundances, an improved modeling of the states of atoms inside the solar plasma is required.